Production and economic viability of banana managed with cover crops - Francisca E. L. Barbosa; Claudivan F. de Lacerda; Aiala V. Amorim; Raimundo N. T. Costa; José A. da Silva; Fernando F. F. Hernandez (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This research aimed to evaluate the yield and economic viability of three crop cycles of the banana cv. ‘Prata Anã’ in association with perennial herbaceous legumes, natural vegetation, or compared with the conventional management. The research was conducted using a complete randomized block design with split-split plots and four replicates. The plots were formed by four irrigation depths: 50, 75, 100 and 125% of crop evapotranspiration, and the subplots by cover crops (Calopogonium muconoides, Pueraria phaseoloides, and natural cover without N addition) or no cover crops with addition of N fertilization (conventional management). The subsubplots were formed by the second, third and fourth banana production cycles. Yield and economic viability of the cultivation were estimated for a period of seven years. The conventional management promoted greater yield and economic viability in the cultivation of ‘Prata Anã’ banana, due to the N fertilization. Managements with leguminous cover crops were also economically viable, but they should be investigated in combination with N fertilization and compared with the conventional method.